SPECIFICITY OF THE TYPE OF WOODWORKING IN FOLK APPLIED DECORATIVE ART - Razzokov Bakhtiyor Khabibullaevich; Sobirov Muzaffar Rakhimjon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
At the moment, such a piece of wood is prepared, which is skillfully processed and such a person can admire, that the language to the tariff is stubborn. Everyone’s labor is valued more expensive than a broken item and patterns are worth a little. As the day new technologies entered our lives, the effectiveness of the use of wood material has arisen. On the equipment, wood is bent, bent, trimmed, shaped, the finished piece is making a lot of us look at our house. In this article, opinions and opinions are made about the specificity of the type of woodworking in folk applied decorative art.